El Sistema de Control Interno Contable y su incidencia en la gestión administrativa y financiera de la Municipalidad Distrital de Guadalupe - 2015 - Urbina Nuñez, Mario Orlando (2016)
This work is an investigation in order to help the process of continuous improvement of the system of accounting control in municipalities, and involves constant evaluation of the operational processes of the entities and municipalities as part of them not being exempted from her, in order to adapt to changes. You must consider information systems that enable accurate and timely information for proper decision making and assess the degree of compliance with the established objectives. The interaction of subsystems and systems operating in the municipalities greatly affect the fulfillment of the vision, mission, objectives and goals. In this context and in line with the research hypothesis: The Internal Accounting Control System if positive impact on the Administrative and Financial Management District Municipality of Guadalupe "- 2015; and according to the results of this investigation; It was achieved to establish that the system of internal accounting control influences and assumes an important role, because through their continuous assessment makes it possible to maximize results in terms of efficiency, effectiveness, economy, equity, ethics and ecology, indicators that strengthen management municipal. In conclusion it is recommended to municipal authorities to design, implement and evaluate an internal control system which becomes the facilitator instrument for achieving the goals, objectives and institutional mission in order to safeguard the assets of the District Municipality of Guadalupe avoiding misuse of money and resources that deteriorate the administrative and financial management of the organization, also recommended to the authorities, officers, employees and residents of the municipalities, work on improving something and compliance controls in place to minimize errors and achieve objectives.